Effects of Moderate- Versus High-Intensity Exercise Training on Physical Fitness and Physical Function in People With Type 2 Diabetes: A Randomized Clinical Trial. Issue 12 (1st December 2014) - Taylor, J. David; Fletcher, James P.; Mathis, Ruth Ann; Cade, W. Todd
Abstract : Background: Exercise training is effective for improving physical fitness and physical function in people with type 2 diabetes. However, limited research has been conducted on the optimal exercise training intensity for this population. Objective: The primary study objective was to investigate the effects of moderate- versus high-intensity exercise training on physical fitness and physical function in people with type 2 diabetes. Design: This was a randomized clinical trial. Setting: The setting was a university campus. Participants: Twenty-one people with type 2 diabetes were randomly allocated to receive either moderate-intensity training (MOD group) or high-intensity training (HIGH group). Intervention: The MOD group performed resistance training at an intensity of 75% of the 8-repetition maximum (8-RM) and aerobic training at an intensity of 30% to 45% of the heart rate reserve (HRR). The HIGH group performed resistance training at an intensity of 100% of the 8-RM and aerobic training at an intensity of 50% to 65% of the HRR. Measurements: Muscle strength (peak torque [newton-meters]), exercise capacity (graded exercise test duration [minutes]), and physical function (Patient-Specific Functional Scale questionnaire) were measured at baseline and 3 months later. Acute exercise-induced changes in glucose levels were assessed immediately before exercise, immediately after exercise, and 1 hour after exercise during the first exercise training session. Results: Although both groups showed improvements in physical fitness and physical function, the between-group effect sizes were not statistically significant (exercise capacity estimated marginal mean [EMM] difference=2.1, 95% confidence interval [95% CI]=−0.2, 4.5; muscle strength EMM difference=20.8, 95% CI=−23.3, 65.0; and physical function EMM difference=0.1, 95% CI=−0.6, 0.9). Mean percent changes in glucose levels measured immediately before exercise and immediately after exercise, immediately after exercise and 1 hour after exercise, and immediately before exercise and 1 hour after exercise for the MOD group were −11.4%, −5.0%, and −15.8%, respectively; those for the HIGH group were −21.5%, 7.9%, and −15.3%, respectively. Limitations: Sample size, lack of outcome assessor masking, and physical function measurement subjectivity were limitations. Conclusions: Moderate- and high-intensity exercise training, as defined in this study, may lead to similar improvements in physical fitness and physical function in people with type 2 diabetes.